Penegakan Hukum Dalam Penanggulangan Kejahatan Penyalahgunaan Senjata Tajam Oleh Anak Dibawah Umur - Wanda Monica Putri Salsabila; Emilia Susanti; Gunawan Jatmiko; Maroni Maroni; Muhammad Farid (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The aim of this study to understand efforts in combating crimes involving the use of sharp weapons and the inhibiting factors influencing underage individuals in misusing sharp weapons. The method used was a normative juridical approach and an empirical juridical approach with a qualitative research type. Primary and secondary data sources were used. The research results show that the police in preventing and dealing with crimes involving sharp weapon abuse committed by children use a pre-emptive approach, the police focus on identifying potential risks that could cause children to be involved in the misuse of sharp weapons. The preventive approach involves outreach and education activities in the community to increase public awareness about the negative impacts of sharp weapon abuse by children. This study is only related to tackling sharp weapon crimes committed by children. This research contributes by identifying and analyzing various risk factors that contribute to underage individuals engaging in the misuse of sharp weapons, aiding in the development of preventive strategies.